Dos nuevas citas de Lemnaceae para la flora ibérica. - Galán de Mera, Antonio; Aedo, Carlos; Castroviejo, Santiago; Sánchez Pedraja, Óscar (Acta Botanica Malacitana, 2006)
Two new records for Lemnaceae in the Iberian Peninsula Palabras clave. Lemnaceae, Península Ibérica. Key words. Lemnaceae, Iberian Peninsula.